Taphonomy and palaeoecology of Hauterivian-Barremian nerineoid shell beds from the Neuquén Basin, west-central Argentina - Cataldo, Cecilia Soledad (2013)
Nerineoid shell beds are described for the first time from Lower Cretaceous deposits of southern South America. These come from carbonates near the top of the Agrio Formation in southern Mendoza Province, west-central Argentina. To envisage the origin of the nerineoid shell beds, a taphonomic study was carried out, which indicated that these represent within-habitat time-averaged, primary sedimentologic concentrations with a secondary biogenic imprint related to a relatively high local production of nerineoid shells. The associated palaeoenvironments were studied through a facies analysis of the carbonate succession including the shell beds. The carbonates were deposited in a homoclinal ramp system and depict a shallowing upward trend from mid to inner ramp. The individuals lived and accumulated in oolitic shoals within the inner ramp, in a shallow, well-lit, high-energy setting above fair-weather wave base. Substrate was oxygenated and loose. The nerineoids are shown to belong to one species of the genus Eunerinea, and through the functional morphology of the shells they are tentatively interpreted as infaunal or semi-infaunal. It is suggested that the recorded monospecific nerineoid shell beds indicate that the palaeoenvironmental conditions may have been favourable for the development of abundant populations of these gastropods in the northern part of the Neuquén Basin during a short time interval in the Hauterivian- Barremian boundary. This could have been related to a brief warming episode but other factors may have also been involved.